The Effect of Ease and Benefits of Using Accounting Information Systems on Employee Performance - Hilda Novitasari; Syarifuddin; Aini Indrijawati (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to examine and analyze the effect of the ease and benefits of using an accounting information system (AIS) on employee performance. Data collection was carried out using a questionnaire which was distributed to 108 employees using ERP-SAP (Enterprise Resource Planning-System Application an Product) at PT ASDP Indonesia Ferry (Persero) Region III and Region IV. The data that has been obtained was analyzed using SEM (Structural Equations Modeling) through the Amos 22 program. The results showed that the ease of use of accounting information systems and the benefits of using accounting information systems have a positive and significant effect on employee performance